THE IDEOLOGICAL CONTENT AND POWER STRUCTURE BEHIND THE TRANSFORMATION OF THE OUTPOURING OF HUMAN LABOR - Tashya Panji Nugraha (Jurnal Scientia, 2023)
This study aims to uncover the intrinsic dimensions operating in outsourcing instruments. The approach used in the study is a legal semiotics approach. Research is descriptive-analytical through literature studies by utilizing data such as r. The results of this study state that ideological problems and power structures are identified as operating in outsourcing instruments. Instrumen outsourcing can be used as a vehicle for domination of the interests of the resource ruling class.